Implementation of Interactive Learning Media Wordwall to Improve the Activeness and Cognitive Learning Outcomes of Grade IV Students of SDN Pamotan V in the Science Subject - Diana Kusumaningrum; Laila Nur Vidayanti (Institute of Educational, Research, and Community Service)
Activeness in learning is very important and is the key to the success of learning. Factors that drive this research include lack of student attention during learning, low student involvement in the learning process, and low use of media during classroom learning activities. The purpose of this study was to determine whether the use of wordwall as an interactive learning media in the learning process can improve the activeness and cognitive learning outcomes of students in grade IV of SDN Pamotan V in science subjects. Classroom action research (CAR) is the type of research used. The CAR model used is the Suharsimi Arikunto model. Cycle I and Cycle II of the study involved planning, implementation, observation, and reflection. This study collected data using interviews, observation sheets, tests, and documentation. The results showed that interactive wordwall learning media can improve the activeness and learning outcomes of grade IV students in science subjects. In cycle I, student activeness reached 97% with a very good score, and in cycle II, student activeness reached 88.2% with a very good score. The improvement of students' cognitive learning outcomes can be seen through the gain test score, namely in cycle I it produces a gain score test result, namely a normalized score of 0.47 which is categorized as moderate and in cycle II it obtains a normalized score of 0.69 with a moderate category. Therefore, wordwall is an interactive learning media, wordwall can be used to improve students' activeness and cognitive learning outcomes